Workplace violence against Chinese health professionals 2013–2021: A study of national criminal judgment documents - Xiao, Yu; Chen, Ting-ting; Zhu, Shao-yi; Zong, Ling; Du, Na; Li, Chun-ya; Cheng, Hao-fei; Zhou, Qi; Luo, Li-shi; Jia, Juan (Frontiers in Public Health, 2022)
Objectives: Patient-initiated hospital violence is a global problem which threatens the safety of health professionals and is indicative of doctor-patient tensions, impeding health system quality and access. The current study aimed to improve the understanding of medical workplace violence (WPV) in China, using authoritative and nationally representative judgment records, and to approach violence prevention strategies. Methods: All litigation records relating to violence against health professionals between 2013 and 2021 were extracted from the China Judgment Online System. Basic case information, victim characteristics, perpetrator characteristics and the nature of the violence were collated. The relationship between different treatment outcomes and violence was also explored. Results: Numbers of cases of hospital violence gradually increased from 2013 to a peak in 2016 before gradually decreasing in the following years. The most common perpetrators were patients’ relatives (58.2%), followed by patients themselves (38.2%). Only 9 perpetrators had a confirmed history of mental illness and only two were intoxicated with alcohol. More than half of the cases (52.5%) occurred in rural areas and this percentage is even greater for primary health care institutions (71.4%) and secondary hospitals (73.5%). On a departmental level, the highest incidence of medical WPV was found in the emergency (18.9%), pediatrics (13.2%) and obstetrics (11.5%) departments. Violent behaviors, such as stalking, mass occupation of the ward and sharp instrument injury were significantly related to cases not involving patient death (p < 0.05). Disruptive behavior, such as hanging banners, blocking hospital passages, placing flower wreaths and burning paper money were significantly correlated with cases involving patient death (p < 0.01). The interval between a patient's death and the ensuing violence was short, happening on the same day in 54.8% of cases. Conclusions: A comprehensive overview of medical WPV in China is presented and may have utility for the formulation of prevention strategies.